THE FIRST RECORD OF A LATE TITHONIAN AMMONITE IN THE FEODOSIYA SECTION OF EASTERN CRIMEA - Arkadiev V.V. (My University, 2004)
A Late Tithonian ammonite, Oloriziceras schneidi Tavera, 1985, is recorded for the first time in the Feodosiya section of the Tithonian - Berriasian boundary beds of Eastern Crimea
Keywords: ammonites; Late Tithonian; Feodosiya section; Eastern Crimea; Mesozoic::Jurassic::Upper::Tithonian; Мезозой::Юрская::Верхний::Титонский